The Affect of Pentoxifylline on Sperm Parameters in Normozoospermic, Asthenozoospermic and Oligo-Asthenozoospermic Males - Çetintaş, Süheyla; Esinler, İbrahim and Durak, Tülay and Öktem, Mesut and Kuşçu, Esra and Zeyneloğlu, Hulusi (Gynecology Obstetrics & Reproductive Medicine, 2007)
OBJECTIVE: To determine the affect of pentoxifylline (PTX) on sperm parameters in normozoospermic, asthenozoospermic, and oligo-asthenozoospermic males. STUDY DESIGN: Each semen sample collected from normozoospermic (n=20), asthenozoospermic (n=20), and oligo-asthenozoospermic (n=20) males was divided into two equal parts. One part of the semen sample washed using Puresperm only (NidaCon, Sweden) (After-wash category) and other part was treated with pentoxifylline after washing with Puresperm (PTX-treated category). The semen parameters of the after-wash and PTX-treated categories were compared. RESULTS: PTX-treated category was demonstrated significant increment of sperm concentration and rate of sperm with intact acrosome (SIA) when compared to after-wash group in both asthenozoospermic and oligo-asthenozoospermic males. In addition, PTX-treated group resulted higher sperm morphology in oligo-asthenozoospermic males when compared to after-wash group. However, PTX did not show any superiority on after-wash group in normozoospermic males. CONCLUSIONS: Pentoxifylline have beneficial effect on sperm parameters especially in oligo-asthenozoospermic and asthenozoospermic patients.